2018
DOI: 10.1080/09513590.2018.1460341
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of polycystic ovary syndrome (PCOS) associated with CC genotype of miR-146a gene variation

Abstract: Polycystic ovary syndrome (PCOS) is an endocrinopathy in reproductive-age women believed to be affected by several genetics and environmental factors or both. Different miRNAs are one of such genetic factors that their associations with PCOS have been implicated. For instance, miR-146a that is well known for strongly regulating the immune response and inflammation was upregulated in serum plasma, follicular fluid and granulosa cells of PCOS patients. Different studies have shown that genetic changes in pre-miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Hosseini et al in a study investigating the association of miR-146a and miR-222 polymorphisms with susceptibility to PCOS demonstrated the significant correlation of both SNPs with an increased risk of PCOS [ 17 ]. Similar to our results, Ebrahimi and others found a significantly higher rate of miR-146a variant incidence in cases compared to controls and considered miR-146a variation to lead to increased PCOS among their studied group [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Hosseini et al in a study investigating the association of miR-146a and miR-222 polymorphisms with susceptibility to PCOS demonstrated the significant correlation of both SNPs with an increased risk of PCOS [ 17 ]. Similar to our results, Ebrahimi and others found a significantly higher rate of miR-146a variant incidence in cases compared to controls and considered miR-146a variation to lead to increased PCOS among their studied group [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Of these, 975 were excluded after title/abstract screening (not relevant to the review inclusion criteria). We examined the full text of 52 publications to summarize the possible translational role of miRNA in PCOS [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , …”
Section: Resultsmentioning
confidence: 99%
“…Studies among women with PCOS have observed the upregulation of miR‐146a in granulosa cells, follicular fluid, and serum 119 . Bioinformatic data suggest that the target genes of miR‐146a are involved in cell cycle, apoptosis, and endocrine signaling pathways (e.g., Jak‐STAT, Wnt, and MAPK), indicative of the association of miR‐146a with pathogenesis of PCOS 17 .…”
Section: Inflammationmentioning
confidence: 99%
“…Bioinformatic data suggest that the target genes of miR‐146a are involved in cell cycle, apoptosis, and endocrine signaling pathways (e.g., Jak‐STAT, Wnt, and MAPK), indicative of the association of miR‐146a with pathogenesis of PCOS 17 . Iranian studies have reported that the miR‐146a rs2910164 polymorphism is associated with a higher risk of PCOS 119,120 …”
Section: Inflammationmentioning
confidence: 99%